2022
DOI: 10.22514/jocpd.2022.002
|View full text |Cite
|
Sign up to set email alerts
|

Does selective caries removal in combination with antimicrobial photodynamic therapy affect the clinical performance of adhesive restorations of primary or permanent te eth? A systematic review with meta-analysis

Abstract: Antimicrobial photodynamic therapy (aPDT) is an adjunct to a selective caries removal (SCR) technique for deep caries lesion treatment. The knowledge about chemical and structural changes affecting the remaining dentin surface after the use of this therapy is still unknown. Objective: to answer the following question: Does the SCR technique in combination with aPDT affect the clinical performance of adhesive restorations in deep carious lesions of primary or permanent teeth? Study design: a systematic review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the bactericidal effect of bio-inductive materials on cariogenic bacteria is unknown because there was no report examining the antimicrobial properties of bio-inductive materials. Meanwhile, the bactericidal effect of aPDT on cariogenic bacteria has attracted much attention, and many basic and clinical studies have been conducted [ 17 , 18 , 19 ]. Although the results of these studies all suggested that aPDT was effective in the treatment of dental caries, the kinds of photosensitizers and types and wavelengths of light sources used in these studies varied widely.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bactericidal effect of bio-inductive materials on cariogenic bacteria is unknown because there was no report examining the antimicrobial properties of bio-inductive materials. Meanwhile, the bactericidal effect of aPDT on cariogenic bacteria has attracted much attention, and many basic and clinical studies have been conducted [ 17 , 18 , 19 ]. Although the results of these studies all suggested that aPDT was effective in the treatment of dental caries, the kinds of photosensitizers and types and wavelengths of light sources used in these studies varied widely.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, minimally invasive dentistry should be a guide mark to restore dental caries and there are new procedures that offer advantages over conventional methods. Although selective procedures are well documented in the literature, with respect to deciduous teeth, there are few investigations about these techniques in permanent dentition [ 14 ]. Since both dentitions present differences, such as size of teeth or regenerative potential, they should be studied separately.…”
Section: Introductionmentioning
confidence: 99%